2001
DOI: 10.1212/wnl.56.10.1399
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of pergolide in the treatment of restless legs syndrome

Abstract: An open follow-up of a controlled study in patients with restless legs syndrome (RLS) shows that the beneficial effect of pergolide on RLS symptoms persists throughout at least 1 year. Twenty-two patients of 28 (78.6%) continued to take pergolide. Polysomnographic measurements showed a persistent improvement of PLM index, PLMS arousal index, total sleep time, and sleep efficiency (p = 0.0001). Side effects, in particular nausea, were common but were well controlled by domperidone in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 10 publications
1
42
1
1
Order By: Relevance
“…Another major finding of this study is that a single evening dose of pramipexole alleviated daytime symptoms in all patients who had previously developed augmentation under levodopa and thus pramipexole is an interesting alternative in this subgroup of patients. Pramipexole seems to have several advantages: (a) since a low dose of pramipexole is already effective, there is no need for the long titration period usually necessary when patients receive longer-acting dopamine agonists such as pergolide [22] or cabergoline [7]; (b) dopaminergic side-effects seem to be rare, and in the presented study it was not necessary to administer pramipexole in combination with domperidone (domperidone is usually prescribed in pergolide-treated patients to limit peripheral dopaminergic side-effects [22,23]), and (c) the possible antidepressive effect of pramipexole as seen in patients with major depression [24]. Depression seems to be more frequent in RLS [25] and it has already been demonstrated that RLS patients improve on the Zung Self-Rating Depression Scale [26] when taking pramipexole [12].…”
Section: Discussionmentioning
confidence: 99%
“…Another major finding of this study is that a single evening dose of pramipexole alleviated daytime symptoms in all patients who had previously developed augmentation under levodopa and thus pramipexole is an interesting alternative in this subgroup of patients. Pramipexole seems to have several advantages: (a) since a low dose of pramipexole is already effective, there is no need for the long titration period usually necessary when patients receive longer-acting dopamine agonists such as pergolide [22] or cabergoline [7]; (b) dopaminergic side-effects seem to be rare, and in the presented study it was not necessary to administer pramipexole in combination with domperidone (domperidone is usually prescribed in pergolide-treated patients to limit peripheral dopaminergic side-effects [22,23]), and (c) the possible antidepressive effect of pramipexole as seen in patients with major depression [24]. Depression seems to be more frequent in RLS [25] and it has already been demonstrated that RLS patients improve on the Zung Self-Rating Depression Scale [26] when taking pramipexole [12].…”
Section: Discussionmentioning
confidence: 99%
“…The most common prescriptions were for benzodiazepines, presumably as these agents alleviate the secondary sleeprelated symptoms common among RLS sufferers. That very few physicians were prescribing dopamine agonists and L-dopa is perhaps not surprising as the study period predates the publication of many clinical trials demonstrating the efficacy of these drugs [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…It has demonstrated good efficacy in several small clinical trials. [21][22][23] However, ergot-derived dopamine agonists such as pergolide carry the potential risk of fibrotic complications and may be associated with valvular heart disease. 24 As the dopamine agonists ropinirole and pramipexole are not ergot-derived, they are not typically associated with the risk of structurally related fibrotic complications.…”
mentioning
confidence: 99%